Nb-Ta-Sn Oxides from Lithium-Beryllium-Tantalum Pegmatite Deposits of the Kolmozero–Voronja Belt, NW Russia: Implications for Tracing Ore-Forming Processes and Mineralization Signatures - Dmitry Zozulya; Lyudmila N. Morozova; Kåre Kullerud; Ayya Bazai (Geosciences, 2023)
In this paper we present textural and compositional data for columbite group minerals (CGMs) and associated Nb-Ta-Sn oxides from lithium-beryllium-tantalum pegmatite deposits of the Kolmozero–Voronja belt, NW Russia, with the aim of deciphering these characteristics for minerals from deposits with different mineral signatures and lithium ore grade. Minerals from four deposits, including two of world-class (Kolmozero and Polmostundra), are examined. The main controlling factors for CGM compositional ranges are the diversity and rate of magmatic fractionation, hydrothermal overprint and mineral paragenesis, following the specific geochemical signature of the different pegmatite deposits. CGM from Kolmozero include several mineral species (columbite-(Fe), columbite-(Mn), tantalite-(Fe), and tantalite-(Mn)), showing large compositional variations, mainly controlled by Nb-Ta fractionation (Ta/(Ta + Nb) = 0.16–0.70; Mn/(Mn + Fe) = 0.45–0.63). Textural patterns are various (oscillatory, homogeneous, and patchy); spongy domains and overgrowing Ta-rich rims are also observed somewhere. This indicates the involvement of numerous magmatic and hydrothermal processes. The Polmostundra CGMs are represented by columbite-(Fe) with Ta/(Ta + Nb), ranging from 0.05 to 0.39; some crystals are homogenous, and others present normal, oscillatory, mottled and reverse-zoning patterns. The Okhmylk CGMs are irregular normal, patchy and homogeneous columbite-(Fe) and columbite-(Mn), with Ta/(Ta + Nb) = 0.09–0.24 and Mn/(Mn + Fe) = 0.29–0.92, indicating the suppressed magmatic fractionation and iron drop due to precipitation of Fe minerals. Columbite-(Fe) and columbite-(Mn) from the Be-Ta Shongui deposit are less evolved, with Ta/(Ta + Nb) = 0.07–0.23 and Mn/(Mn + Fe) = 0.31–0.55. The minerals are characterized by progressive normal, oscillatory, homogeneous and irregular reverse patterns. Associated pyrochlore minerals occur both as early magmatic (Kolmozero) and late hydrothermal (Polmostundra, Okhmylk). Cassiterite is found only in the Okhmylk dykes, and is apparently of hydrothermal origin. CGM from Li pegmatites have impurities of Ti (0.01–0.05 apfu) and W (up to 0.02 apfu), whereas CGM from Be pegmatites contains elevated Ti (up to 0.09 apfu). The mineral system analysis presented here is relevant for exploration.